Commentary: A Radiologist's Guide to Peer-Reviewing Manuscripts. Issue 2 (26th March 2023) - Ersahin, Devrim; Catanzano, Tara; Tamm, Eric
Abstract: Reviewers play an important role in the publishing of radiology articles. When done well, reviewers help editors identify which articles to accept and improve them through their recommendations. In this commentary, we provide a step-by-step guide to reviewing both original science and review articles.